Post Partum Pyometra In Iraqi Buffaloes : Clinical and Therapeutical Study: A.Sh.Sultan ;AL-hamedawi ; T.M. and S.O. Hussain - Sultan, A. Sh. (The Iraqi Journal of Veterinary Medicine, 2005)
The study was conducted on 118 buffaloes suffering from openedpyometra 20-30 days post partum in AL-thahab AL-abiadh village west ofBaghdad Province, their ages ranged from 3-6 years.They were divided randomly in to 4 groups . Group one included (27 buffalo)treated with 15 mg of PGF2α ( Prosolven )R IM, The 2nd group (32 buffalo)treated with 15 mg of PGF2α and 15 mg estradiol benzoate IM . The 3rd group(29 buffalo) treated with 15 mg of PGF2α and 50 . 100 ml of lugol’s iodine 0.5% intra-uterine.The 4th group (30 buffalo) treated with 15 mg of PGF2α and 4 gm ofOxyteracycline 20% (20 ml of Oxy. plus 50-100 ml disilled water) intra-uterine.Results showed that the 1st and 2nd response in 4 treated groups were66.2%, 84.3%, 79.3% and 86.6% respectively .The response was high in the 2ndand 4th group (P < 0.01). These responses represent also the conception rate forthese 4 treated groups. The means ± SE of days open for above groups were98.4± 6.4 ,84.2 ± 4.4 ,97.3 ± 3.8 and 82.7 ± 4.6 respectively ,the second andfourth group were significant (P < 0.01).The number of newly born calves was 94 calves (46 male,48 female) Thealive were 87(92.6%) and dead 7 (7.4%), so we conclude that the PGF2α has aneffective role in the treatment of pyometra in buffalo and it’s effect increasingwhen it combined with oxytetracycline 20% and estradiol benzoate together .